Development of Roadmap for the Aircraft Maintenance Industry, Maintenance Repair & Overhaul/MRO, in Indonesia - Freddy Franciscus (Jurnal Inovasi Teknologi, 2021)
Based on data from IAMSA in 2019, prior to the COVID-19 pandemic, the volume of aircraft maintenance spending from airlines in Indonesia was around US$ 1.2 billion. Of the spending volume, only about 35% can be absorbed by MRO Indonesia. MRO Indonesia has targeted in the next 5 years it can absorb around 70% of aircraft maintenance expenditures in Indonesia. The purpose of this paper is to build a roadmap for the aircraft maintenance industry in Indonesia. A road map is a guide that is used as directions/navigation to reach the desired target. The development of a roadmap for the aircraft maintenance industry in Indonesia is carried out by taking into account the current condition of Indonesia's MRO and future Indonesia’s MRO targets in absorbing aircraft maintenance spending in terms of the 4 main pillars of the MRO industry, namely quality, human resources, infrastructure and supply chain. In terms of quality, it is necessary to increase the level of Indonesian MRO certification to the level of international standards (AS 9110, EASA, FAA). In terms of human resources, it is necessary to increase the number of licensed technicians by collaborating between MRO and vocational education institutions. In terms of infrastructure and supply chain, it is necessary to build hangars and workshops that have an integrated aircraft maintenance center facility 'one stop solution'/aerospace park. The strengthening of the four pillars is carried out gradually and continuously according to priorities to form a roadmap for the aircraft maintenance industry in Indonesia.